The Effect of Extra Virgin Olive Oil (EVOO) on Expression of Vascular Endhothelial Growth Factor (VEGF) and Arteriole Number on Endometrium of Female Rattus norvegicus of Wistar Strain Exposed to Rhodamin B - Anisak, Siti; Sujuti, Hidayat; Sutrisno, Sutrisno; Mintaroem, Karyono; Nurseta, Tatit; Kalsum, Umi (Health Notions, 2018)
.